INTEGRASI KEARIFAN LOKAL TE ARO NAWEAK LAKO DALAM PENDIDIKAN KARAKTER DI SEKOLAH DASAR - Gombo, Mikaus (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to integrate the local wisdom of Te Aro Naweak Lako into character education at elementary schools in Wamena, Jayawijaya Regency, Papua. Te Aro Naweak Lako embodies the values of empathy (naweak) and togetherness (lako), which align with the goals of character education to develop students who are virtuous and socially caring. The implementation methods include teacher training, development of learning modules based on local culture, classroom mentoring, and evaluation through observation and interviews. Teachers from three elementary schools actively participated in this process. The results showed an increased understanding among students of the values of empathy, responsibility, and cooperation. This activity also strengthened the relationship between schools and the indigenous community by involving local leaders who revived folk stories and communal work practices (gotong royong), which have increasingly been marginalized by modernization. Student character evaluations indicated significant improvements in empathy, responsibility, cooperation, and cultural appreciation. Teachers and parents expressed appreciation for this approach because it is more contextual and has a direct impact on student behavior both at school and at home. This activity recommends replicating the Te Aro Naweak Lako model in other schools across the Papua highlands as a means of cultural preservation and strengthening character education based on local wisdom.